Response of young apricot trees to natural zeolite, organic and inorganic fertilizers - T. Milošević; N. Milošević (Plant, Soil and Environment, 2013)
The study focused on characterizing five apricot cultivars to acknowledge the impact of natural zeolite (Agrozel type), cattle manure, composite NPK (15-15-15) and calcium ammonium nitrate (CAN) on tree vigour, precocity, yield performance and fruit quality attributes. The results showed that Agrozel induced the highest tree growth in all cultivars, yield and cumulative yield in Vera, Harcot and Roxana and yield efficiency in Aleksandar, Vera and Roxana. The higher fruit weight of all cultivars was found after the manure application. Composite NPK plays a major role in soluble solids, total sugars and titratable acidity accumulation, whereas CAN and Agrozel applications resulted in a higher soluble solids/titratable acidity ratio and flesh firmness in most of the cultivars.